Acute appendicitis complicated by ovarian vein thrombosis - Talreja, Deep P.; Talreja, Rani B.; M. Elsayed, Ahamed; Parkash, Simran; M. Al-Qanubi, Ismail; Albatanony, Ayman A. (International Surgery Journal, 2023)
Ovarian vein thrombosis (OVT) is a rare cause of acute abdominal pain and is mainly related to pregnancy and affects approximately 1 in every 2,000 deliveries and abortions. However, this diagnosis should be considered not only in postpartum patients but also in women with pelvic inflammatory disease (PID), malignancy, women who have recent abdominal surgery and who have a known hypercoagulable state. Anticoagulation and antibiotics are the mainstays of treatment for OVT. Complications of OVT include sepsis, the extension of the thrombus to the inferior vena cava and renal veins, and pulmonary embolism. The incidence of pulmonary embolism is reported to be 13.2% and represents the main cause of mortality due to OVT. We report a case of 40-years old female patient presenting with OVT, which was accompanied by acute appendicitis. In this woman, OVT was not related to pregnancy. The patient underwent an appendectomy, which proved positive on histopathology result. Patient symptoms improved after appendectomy with antibiotics and anticoagulation therapy. A month later, a follow-up computed tomography (CT) scan of the abdomen revealed a complete resolution of OVT. OVT, though a rare presentation, should be included in the differential diagnosis for women presenting with acute abdomen. Proper diagnosis and timely management can prevent catastrophic complications. Our case thus highlights the importance of considering the rare diagnosis of OVT with acute appendicitis.